Sustainable performance evaluation according to the Global Reporting Initiative (GRI) standards at Fadak Agricultural Company (Journal of Accounting and Financial Studies ( JAFS ), 2024)
This research aims to shed light on the concept and motives of adopting sustainable performance reporting in accordance with the GRI Global Reporting Initiative and its role in communicating information to stakeholders to enable them to form an integrated picture of the performance of oil companies. To improve the quality of reporting by reducing the shortcomings of financial reporting through the development of sustainable reporting.The deductive approach was used in the theoretical aspect of the research to reach the latest findings of the world in the field of reporting on sustainable performance and their relationship to the creation of value for economic units and methods of reporting. The inductive and analytical method of research was used in its practical aspect to study the relationship of sustainable performance according to the standards of the global initiative GRI in the development of a report on the performance of FDK agricultural company.One of the most important conclusions reached in this research is that the sustainable report helps the economic unit research sample in revealing the unforeseen current problems as well as the expected future problems that are not provided by traditional financial reporting. The higher the level of reporting of non-financial reports by economic units, this will leave a positive impression on the efficiency and effectiveness of social performance among customers, and this in turn will lead to an increase in the value of the company.